IMPLEMENTASI AKUNTABILITAS PELAPORAN KEUANGAN GKJ NEHEMIA JAKARTA - Gratia Wardani, - (2019)
As an example of a non-profit organization, the church needs a resource to carry out its operational activity. The basic difference lies in how a church obtains its resources, where the church gathers its resources from the congregation who do not expect anything in return. Therefore, as a form of responsibility and a good governance principle, the church has a responsibility to give accountability to the congregation, including its financial reporting. This study was conducted to describe how Javanese GKJ Nehemia, Jakarta applied accountability seen from its financial aspect. The methodology for this study is a qualitative methodology, with a phenomenological approach to seek the meaning of an object or phenomena based on an experience from the other people. The data collected using several methods: literature study, observation, and in-depth interview with key and supporting informant. The result from this study shows: (1) Financial report accountability from GKJ Nehemia presented through several stages: budget planning and approval process, implementation of church activities, financial reporting, (2) reporting standard used in GKJ Nehemia are not using PSAK No.45, (3) Financial report conducted by GKJ Nehemia has been carried out accountable, (4) The congregation still can't feel the transparency from GKJ Nehemia.